Differential Regulation of Echinocandin Targets Fks1 and Fks2 in Candida glabrata by the Post-Transcriptional Regulator Ssd1 - Kelley R. Healey; Padmaja Paderu; Xin Hou; Cristina Jimenez Ortigosa; Nicole Bagley; Biren Patel; Yanan Zhao; David S. Perlin (Journal of Fungi, 2020)
Invasive infections caused by the opportunistic pathogen Candida glabrata are treated with echinocandin antifungals that target β-1,3-glucan synthase, an enzyme critical for fungal cell wall biosynthesis. Echinocandin resistance develops upon mutation of genes (FKS1 or FKS2) that encode the glucan synthase catalytic subunits. We have analyzed cellular factors that influence echinocandin susceptibility and here describe effects of the post-transcriptional regulator Ssd1, which in S. cerevisiae, can bind cell wall related gene transcripts. The SSD1 homolog in C. glabrata was disrupted in isogenic wild type and equivalent FKS1 and FKS2 mutant strains that demonstrate echinocandin resistance (MICs ˃ 0.5 µg/mL). A reversal of resistance (8- to 128-fold decrease in MICs) was observed in FKS1 mutants, but not in FKS2 mutants, following SSD1 deletion. Additionally, this phenotype was complemented upon expression of SSD1 from plasmid (pSSD1). All SSD1 disruptants displayed susceptibility to the calcineurin inhibitor FK506, similar to fks1∆. Decreases in relative gene expression ratios of FKS1 to FKS2 (2.6- to 4.5-fold) and in protein ratios of Fks1 to Fks2 (2.7- and 8.4-fold) were observed in FKS mutants upon SSD1 disruption. Additionally, a complementary increase in protein ratio was observed in the pSSD1 expressing strain. Overall, we describe a cellular factor that influences Fks1-specific mediated resistance and demonstrates further differential regulation of FKS1 and FKS2 in C. glabrata.